ANALYTICAL STANDARDIZATION OF TRIPHALADI TAILA - Pudi, *Ramkumar; Sridurga, Ch. (International Journal of Ayurveda and Pharma Research, 2018)
Analytical study plays an important role in the standardization of the drugs. Ayurveda, the ancient system of medicine is gaining recognition throughout the world and many herbal, metal and mineral drugs are now clinically tested and accepted. However, one of the impediments in the acceptance of the ancient systems of medical preparation is the lack of standard quality control profiles. The quality of the drugs, that is, the profile of the constituents in the final product has implication in efficacy and safety. The Sneha kalpa are par excellent to other dosage forms due to their wider advantages like increased absorption and extraction of fat soluble active principles. Sneha kalpas are the only dosage from which can be administered conveniently both internally as well as externally. Triphaladi Taila is an important herbo mineral formulation mentioned in Rasaratnakara indicated for the management of the disease Palitya as Kesharanjaka. The ingredients present in the “Triphaladi Taila” are Sodhita Lauha churna, Triphala churna, Bhringaraja swarasa and Tila taila. Shodhana, Swarasa nirmana, Kalka nirmana, Churna nirmana and Snehapaka and are the main pharmaceutical procedures employed in the preparation of Triphaladi Taila. To assess the safety and to understand the physico chemical properties, organoleptic tests, moisture content, refractive index, fat, Iodine value, pH value, Saponification value, Acid value, ash value, weight/ml, viscosity, iron, volatile oil and microbial tests as well as chromatographically (TLC) for developing standards.